MEF adaptee a I' evaluation des actions exercees par un materiau pulverulent aux parois d 'un silo - Ragneau, Eric; Aribert, Jean-Marie (European Journal of Computational Mechanics, 1995)
The paper deals with the description of a suitable finite element method for an accurate simulation of grain action along the walls of silos. The model allows to compute the stress distribution inside the silo during the filling and the discharging stages. To simulate the filling, the finite element layers are set in action progressively, and at the discharging stage, the computation is based on efficient assumptions about the boundary conditions along the interface between the flow area and the dead zone. The main conditions to satisfy for a significant calculation of stresses along the silo wall are related to the very non linear constitutive law of the ensiled material, and with the friction law at the wall. In the second part of the paper, comparisons are made to show the good agreement between the computed solutions and stress measurements carried out during full scale tests. The FEM has also been used to establish the basic assumptions of simplified analytical solutions in order to improve the actual silo design.